PENGUKURAN NILAI METABOLIT PADA PENGGUNAAN VARIASI NILAI TIME ECHO PEMERIKSAAN MAGNETIC RESONANCE SPECTROSCOPY OTAK - Agi Febrian Trihadijaya; Bagus Abimanyu; Darmini Darmini (Jurnal Imejing Diagnostik (JImeD), 2019)
Background : Application of MRS itself to measure the N-Acetyl Aspartate (NAA) content in tumour, stroake and epilepsy. Contents of NAA has important role in the central nervous system. Examination of MRS itself should be included to support the patient diagnose. Time echo is an important parameter which affect the metabolite spectrum. So, measurement of metabolic value using variants of TE which is 35, 144, 288 ms, are the main idea. The purpose of this research to know the measurable metabolic which use of variants of TE and to know which TE has show the smallest difference with normal metabolic value.Methods : This research is a quantitative descriptive method. Reasearch subject is Radiographer which has competence dan enough experience in MRI. Research samples using 10 person who become the research probandus. The acquisition is do three times on right temporal lobe with TE value 35, 144 and 288 ms. Another parameter which controlled is TR 2000 ms, Single Voxel Spectroscopy (SVS) acquisition sized 31.7mm3 with Point Resolved Spatial Selection (PRESS) pulse sequence. Measurable metabolic aspect which will be evaluate is N-Acetyl aspartate (NAA), Choline (Cho) and Creatine (Cr). Data processing and analysis is do by calculate the spectroscopy spectrum intensity so obtained the measurable metabolic value then using univariate analysis or descriptive analysis.Results : Results of measurable metabolites is the longer TE use so the metabolic spectrum will be decrease on NAA (35 ms: 8.2, 144 ms: 7.3, 288 ms: 5.4), Cr (35 ms: 6.8, 144 ms: 5.8, 288 ms: 3.8) and Cho (35 ms: 6.9, 144 ms: 6.0, 288 ms: 4.4). Then on the calculate of metabolic value difference with normal metabolic value, the longer TE use so the difference will be increase on NAA (35 ms: 1.8, 144 ms: 2.7, 288 ms: 4.6), Cr (35 ms: 1.2, 144 ms: 2.2, 288 ms: 4.2) and Cho (35 ms: 0.1, 144 ms: 1.0, 288 ms: 2.6).Conclusion : So can be assumed that using TE 35 ms on MRS will obtain the metabolic spectrum which close to normal metabolic value. But, short TE unable to show the Lactate spectrum in case of brain tissue abscess, so it’s required to scanning using TE 35 ms and 144 ms or 288 ms as comparison to get more accurate measurable metabolic value.